Modeling InSAR Phase and SAR Intensity Changes Induced by Soil Moisture - Eshqi Molan, Yusuf; Lu, Zhong (IEEE transactions on geoscience and remote sensing, 2020)
A broad range of studies have been conducted so far to quantify the effect of soil moisture on synthetic aperture radar (SAR) intensity and interferometric synthetic aperture radar (InSAR) phase. The introduced models are either intensity or interferometric models, and there is no single scattering model that can estimate both intensity and phase changes, indicating the subject is poorly understood. Here, we quantify the influence of soil moisture on InSAR phase and SAR intensity by employing a volume scattering model. We model soil as a collection of randomly distributed independent point scatterers embedded in a homogeneous background. Our volume scattering model successfully estimates SAR intensity and InSAR phase changes due to soil moisture changes. In addition to soil moisture changes, the model also takes into account the scatterers' size and their volumetric fraction. This may open a new window in the study of soil structure using SAR images and InSAR methods. Our results indicate that the structure of soil manipulates the way soil moisture alters the SAR intensity and InSAR phase. The model has been evaluated against field soil moisture measurements and shown to be successful in modeling InSAR phase and SAR intensity.